2009
DOI: 10.1254/jphs.08322fp
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Mitochondrial Energy-Producing Ability in the Development of Right Ventricular Failure in Monocrotaline-Induced Pulmonary Hypertensive Rats

Abstract: Abstract. The present study was undertaken to explore the possible involvement of alterations in the mitochondrial energy-producing ability in the development of the right ventricular failure in monocrotaline-administered rats. The rats at the 6th week after subcutaneous injection of 60 mg/kg monocrotaline revealed marked myocardial hypertrophy and fibrosis, that is, severe cardiac remodeling. The time-course study on the cardiac hemodynamics of the monocrotalineadministered rat by the cannula and echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…83 In contrast, in monocrotaline-induced RVH, decreases in both phosphocreatine and ATP levels were observed. 82 Right ventricular dysfunction is associated with increased glycolysis Takeyama et al 85 observed that glucose uptake was increased in the right ventricle of conscious rats 4 weeks after pulmonary constriction (using 14 C-2 deoxyglucose [2DG]). There was no difference in 14 C β-methylheptadecanoic acid (BMHDA) accumulation, suggesting no differences in fatty acid uptake between sham and hypertrophied right ventricles.…”
Section: Cardiac Metabolism In Right Heart Failurementioning
confidence: 99%
“…83 In contrast, in monocrotaline-induced RVH, decreases in both phosphocreatine and ATP levels were observed. 82 Right ventricular dysfunction is associated with increased glycolysis Takeyama et al 85 observed that glucose uptake was increased in the right ventricle of conscious rats 4 weeks after pulmonary constriction (using 14 C-2 deoxyglucose [2DG]). There was no difference in 14 C β-methylheptadecanoic acid (BMHDA) accumulation, suggesting no differences in fatty acid uptake between sham and hypertrophied right ventricles.…”
Section: Cardiac Metabolism In Right Heart Failurementioning
confidence: 99%
“…Impairment of oxygen consumption and energy production was shown to correlate with exacerbation of heart function in pulmonary arterial hypertension (PAH)-induced right ventricular (RV) failure [24]. A more detailed examination of energetic dysfunction in a pressureoverloaded rat heart suggested that the transition into heart failure correlates closely with decreases in mitochondrial respiratory capacity [10•].…”
Section: Mitochondrial Dysfunction and Hypertensionmentioning
confidence: 99%
“…Although it is acutely toxic to mitochondria, MCT has no longstanding actions after a single administration and mitochondrial disturbances only develop with PH progression (20).…”
Section: Discussionmentioning
confidence: 99%